2018
DOI: 10.3389/fgene.2018.00366
|View full text |Cite
|
Sign up to set email alerts
|

Computational Tools for Splicing Defect Prediction in Breast/Ovarian Cancer Genes: How Efficient Are They at Predicting RNA Alterations?

Abstract: In silico tools for splicing defect prediction have a key role to assess the impact of variants of uncertain significance. Our aim was to evaluate the performance of a set of commonly used splicing in silico tools comparing the predictions against RNA in vitro results. This was done for natural splice sites of clinically relevant genes in hereditary breast/ovarian cancer (HBOC) and Lynch syndrome. A study divided into two stages was used to evaluate SSF-like, MaxEntScan, NNSplice, HSF, SPANR, and dbscSNV tools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 32 publications
0
61
0
Order By: Relevance
“…In a diagnostic and rapid‐turnover setting, diagnostic laboratories may need to focus on testing the most clinically useful genes. In addition, large comprehensive panels lead to a higher rate of VUS and require continuous research‐based efforts in reclassification . A balance of diagnostic and research goals are encouraged in order to progress in this field.…”
Section: Discussionmentioning
confidence: 99%
“…In a diagnostic and rapid‐turnover setting, diagnostic laboratories may need to focus on testing the most clinically useful genes. In addition, large comprehensive panels lead to a higher rate of VUS and require continuous research‐based efforts in reclassification . A balance of diagnostic and research goals are encouraged in order to progress in this field.…”
Section: Discussionmentioning
confidence: 99%
“…To score the effect on splicing of the CAGI variants from the ENIGMA challenge, we have used the results of our recent work (Moles‐Fernández et al, ) where we identified the best combination of in silico tools for predicting splice site alterations, among those predictors available in the package Alamut Visual v2.10. More precisely, we showed that the HSF+SSF‐like combination (with Δ‐2% and Δ‐5% as thresholds, respectively) for donor sites and the SSF‐like (Δ‐5%) for acceptor sites, exhibited an optimal performance in a benchmark combining RNA in vitro testing and a dataset of variants retrieved from public databases and reported in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…We focused our efforts on the set of BRCA1 and BRCA2 variants provided by the ENIGMA consortium (Spurdle et al, 2012), and we submitted four sets of predictions per protein (Table S1). These four sets correspond to different combinations of our approaches for the prediction of variants leading to affected splicing (AS; one method; Moles-Fernández et al, 2018) or affecting protein function/structure (two methods: MLR and NN). They are the following: 1 Note on terminology: We have italicized the gene symbols (BRCA1 and BRCA2) and not the protein symbols (BRCA1 and BRCA2).…”
Section: Overall Prediction Protocolmentioning
confidence: 99%
See 2 more Smart Citations